15N NATURAL ABUNDANCE OF FOLIAGE AND SOIL ACROSS BOREAL FORESTS OF FINLAND - Sah S.P.; Rita H.; Ilvesniemi H. (My University, 2006)
This study presents the latitudinal variation (from 60° 30′ N to 68° 2′ N latitude) of natural abundances of 15N in the foliage, humus and soils of boreal forests of Finland. Our results clearly showed that N concentration of the foliage did not change significantly with latitudes but their 15N values were significantly higher in higher latitude sites relative to that of the mid and lower latitude sites, indicating the different forms of N uptake at the higher latitudes compared to the lower latitudes. We assume that the higher foliage δ15N values of the higher latitudes trees might be due to either more openness of N cycle (greater proportional N losses) in these latitudes compared to the sites of southern latitudes (lower N losses) or the differences in their mycorrhizal associations. Regression analysis showed that the temperature was the main factor influencing the 15N natural abundance of humus and soil of all forest ecosystems, both before and after clear-cut, whereas rainfall was the main controlling factor to the foliage 15N. Possible reasons behind the increasing δ15N natural abundances of plants and soils with increasing latitudes are discussed in this paper. The clear-cut did not show any specific trend on the 15N fractionation in humus and soil, i.e. both 15N-enrichment and -depletion occurred after clear-cut.
Keywords: 15N NATURAL ABUNDANCE; FOLIAGE; CLEAR-CUT; BOREAL FORESTS; LATITUDES; TEMPERATURES; SOIL